Diagnosis and Control Measures of the 2010 Outbreak of Foot‐and‐Mouth Disease A Type in the Republic of Korea. Issue 2 (27th May 2012) - Park, J. H.; Lee, K. N.; Ko, Y. J.; Kim, S. M.; Lee, H. S.; Park, J. Y.; Yeh, J. Y.; Kim, M. J.; Lee, Y. H.; Sohn, H. J.; Cho, I. S.; Kim, B.
Summary In January 2010, foot‐and‐mouth disease (FMD) occurred for the first time in 8 years in Korea. The outbreaks were because of A serotype, different from the O type, which had occurred previously in 2000 and 2002. The FMD outbreaks were identified in seven farms, consisting of six cattle farms where viruses were detected and one deer farm where only FMDV antibody was detected. The seven farms were within 9.3 km of each other. All susceptible animals within 10 km radius of the outbreak farms were placed under movement restrictions for 3–11 weeks. No vaccination took place to facilitate the clinical observation of infected animals and virus detection. After clinical observations and serological tests within the control zones showed no evidence of FMD infection, the movement restrictions were lifted, followed by FMD‐free declaration (23 March) at 80 days after the first outbreak on 2 January. This communication describes the outbreak of FMD A serotype, and control measures applied to eradicate the disease in Korea.